Collaborative Music‐Making with Digital Audio Workstations: The "nth Member" as a Heuristic Device for Understanding the Role of Technologies in Audio Composition. Issue 3 (5th July 2016) - Brooker, Phillip; Sharrock, Wes
Abstract : This article examines amateur music‐making using a digital audio workstation, showing how audio and software are used as resources for creating compositions. The article has two aims. Firstly, to depict how digital music‐making is formed from routine interactional techniques. Secondly, to probe how researchers might account for such multi‐modal activity through a heuristic device: the " n th member." Whereas sociology has typically been concerned with the cultural facets of how music is made and consumed, we explore the material practices of collaborative song creation utilizing conversation analytic techniques—"turn‐taking" and "next‐selection"—to capture two key interactional moments.